2014
DOI: 10.1021/jp5089965
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Simulations Give Insight into the Hydrogen In and Out Pathways of [NiFe]-Hydrogenases from Aquifex aeolicus and Desulfovibrio fructosovorans

Abstract: [NiFe]-hydrogenases catalyze the cleavage of molecular hydrogen into protons and electrons and represent promising tools for H2-based technologies such as biofuel cells. However, many aspects of these enzymes remain to be understood, in particular how the catalytic center can be protected from irreversible inactivation by O2. In this work, we combined homology modeling, all-atom molecular dynamics, and coarse-grain Brownian dynamics simulations to investigate and compare the dynamic and mechanical properties o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 108 publications
6
44
0
Order By: Relevance
“…As shown in previous mechanical studies done on members of the globin family [39] and homologous hydrogenases [40], proteins with similar folds also present similar rigidity profiles. For each protein fold that was studied, we define the consensus nucleus as the subset of conserved positions along the protein sequence that present rigidity peaks in all (or most of, in the case of largest alignments) the rigidity profiles of the structures that were studied.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…As shown in previous mechanical studies done on members of the globin family [39] and homologous hydrogenases [40], proteins with similar folds also present similar rigidity profiles. For each protein fold that was studied, we define the consensus nucleus as the subset of conserved positions along the protein sequence that present rigidity peaks in all (or most of, in the case of largest alignments) the rigidity profiles of the structures that were studied.…”
Section: Resultssupporting
confidence: 70%
“…In order to investigate them on a residue level, we developed the PROPHET (Probing Protein Heterogeneity) program [37], which combines a coarse-grain (CG) elastic network representation and Brownian dynamics (BD). Studies using PROPHET on various proteins indicate that some residues present specific mechanical properties that can be related to their biological activity, such as catalytic residues [38], residues controlling ligand migration within protein cavity networks [39,40], or residues located on the interdomain interfaces from multi-domain proteins [41,42]. In particular, an early work focusing on haemoproteins [43], and more specifically proteins presenting domains with globin or cytochrome c folds, showed that residues forming the folding nucleus in these two families could be identified via their remarkably high force constants within the protein structure.…”
Section: Introductionmentioning
confidence: 99%
“…Note that the enzyme orientation on the electrode is not only a key issue for interfacial electron transfer, but is also essential to facilitate the diffusion of substrates and products within the enzyme internal cavity network toward the catalytic site. Molecular Dynamics simulations on [NiFe] hydrogenases from A. aeolicus and Desulfovibrio fructosovorans have shown how these two homologous enzymes display their own specific internal tunnel network [31]. In the case of the membrane-bound A. aeolicus hydrogenase, all the substrate entry points are located on the same side Note that the enzyme orientation on the electrode is not only a key issue for interfacial electron transfer, but is also essential to facilitate the diffusion of substrates and products within the enzyme internal cavity network toward the catalytic site.…”
Section: Interfacial Electron Transfer: Why Is Orientation a Key Issue?mentioning
confidence: 99%
“…In the case of the membrane-bound A. aeolicus hydrogenase, all the substrate entry points are located on the same side Note that the enzyme orientation on the electrode is not only a key issue for interfacial electron transfer, but is also essential to facilitate the diffusion of substrates and products within the enzyme internal cavity network toward the catalytic site. Molecular Dynamics simulations on [NiFe] hydrogenases from A. aeolicus and Desulfovibrio fructosovorans have shown how these two homologous enzymes display their own specific internal tunnel network [31]. In the case of the Catalysts 2018, 8,192 7 of 38 membrane-bound A. aeolicus hydrogenase, all the substrate entry points are located on the same side of the enzyme's surface.…”
Section: Interfacial Electron Transfer: Why Is Orientation a Key Issue?mentioning
confidence: 99%
See 1 more Smart Citation